Drug and Disease Model Resources: A Consortium to Create Standards and Tools to Enhance Model‐Based Drug Development. (20th March 2013) - Harnisch, L; Matthews, I; Chard, J; Karlsson, MO
Abstract : Model‐based drug development (MBDD) is accepted as a vital approach in understanding patients' drug‐related benefit and risk by integrating quantitative information integration from diverse sources collected throughout drug development. 1 This perspective introduces the activities of the Drug and Disease Model Resources (DDMoRe) consortium, founded in 2011 through the Innovative Medicines Initiative Joint Undertaking (IMI‐JU) 2 as a European public–private partnership to address a lack of common tools, languages, and standards for modeling and simulation (M&S) to improve model‐based knowledge integration. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e34; doi:10.1038/psp.2013.10 ; advance online publication 20 March 2013